STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGATASI HAMBATAN PEMANFAATAN TIK DAN MENINGKATKAN KOMPETENSI GURU DI SD - Tria Nur Qana’ah; Ahmad Suriansyah; Arta Mulya Budi Harsono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Issues with infrastructure and a lack of qualified staff members are common roadblocks to digital transformation in primary schools. This research seeks to delve into the leadership tactics used by school principals at SDN Karang Mekar 1 Banjarmasin to address obstacles to the utilization of ICT and enhance teachers' digital capabilities. A qualitative method based on a case study design is used in this investigation. Both participant and non-participant observation were used to gather data. The principal served as the policymaker and the teachers as the technical implementers; both roles were represented in the study subjects. Time inefficiency owing to temporary projection equipment and a digital gap between young and older instructors were identified as the biggest hurdles to ICT deployment, according to the findings. To get around this, the principal put a "commitment to competence" policy in place, instituted scheduling-based facilities management, and empowered a "peer coaching" plan as managerial tactics. By working together in this way, skilled educators may help their colleagues who are having trouble with technology. Leadership that is both visionary and collaborative has been shown to increase digital learning efficiency and teacher adaptation in the face of resource constraints, according to this research.